Macromol. Rapid Commun. 8/2013. Issue 8 (14th April 2013) - Yao, Kejian; Chen, Ying; Zhang, Jun; Bunyard, Clay; Tang, Chuanbing
<x xml:space="preserve">Abstract</x> Front Cover: Cationic bottle‐brush polymers exhibit ion‐triggered stimuli‐response. These polymers are synthesized by a combination of ring‐opening metathesis polymerization, ring‐opening polymerization, and click chemistry. With the increase of ionic strength in solution, single brush polymers undergo a transition from extended conformation to collapsed state due to the screening effect of salts that yields once‐dominant electrostatic interactions to hydrophobic–hydrophobic interactions. Further details can be found in the article by K. Yao, Y. Chen, J. Zhang, C. Bunyard, and C. Tang* on page 645. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>